Fluoroquinolone use for uncomplicated urinary tract infections in women: a retrospective cohort study. (May 2020) - Daneman, N.; Chateau, D.; Dahl, M.; Zhang, J.; Fisher, A.; Sketris, I.S.; Quail, J.; Marra, F.; Ernst, P.; Bugden, S.; ,
Abstract: Objectives: The United States Food & Drug Administration released an advisory in 2016 that fluoroquinolones be relegated to second-line agents for uncomplicated urinary tract infections (UTIs) given reports of rare but serious side effects; similar warnings have followed from Health Canada and the European Medicines Agency. The objective was to determine whether alternative non-fluoroquinolone agents are as effective as fluoroquinolones in the treatment of UTIs. Methods: We conducted a retrospective population-based cohort study using administrative health data from six Canadian provinces. We identified women ( n = 1 585 997) receiving antibiotic treatment for episodes of uncomplicated UTIs ( n = 2 857 243) between January 1 2005 and December 31 2015. Clinical outcomes within 30 days from the initial antibiotic dispensation were compared among patients treated with a fluoroquinolone versus non-fluoroquinolone agents. High-dimensional propensity score adjustments were used to ensure comparable treatment groups and to minimize residual confounding. Results: Fluoroquinolone use for UTI declined over the study period in five of six Canadian provinces and accounted for 22.3–48.5% of treatments overall. The pooled effect across the provinces indicated that fluoroquinolones were associated with fewer return outpatient visits (OR 0.89, 95%CI 0.87–0.92), emergency department visits (OR 0.74, 95%CI 0.61–0.89), hospitalizations (OR 0.83, 95%CI 0.77–0.88), and repeat antibiotic dispensations (OR 0.77, 95%CI 0.75–0.80) within 30 days. Conclusions: Fluoroquinolones are associated with improved clinical outcomes among women with uncomplicated UTIs. This benefit must be weighed against the risk of fluoroquinolone resistance and rare but serious fluoroquinolone side effects when selecting first-line treatment for these patients.